A water-soluble fluorescent probe for monitoring mitochondrial GSH fluctuations during oxidative stress. Issue 52 (28th November 2022) - Wang, Huayu; Zhang, Luan; Jin, Xia; Tian, Peijiao; Ding, Xiaojun; Chang, Jing
Abstract : In this research, we constructed a styrylpyridine derivative-based fluorescent probe MITO-PQDNs to monitor mitochondrial glutathione (GSH). Abstract : In this research, we constructed a styrylpyridine derivative-based fluorescent probe MITO-PQDNs to monitor mitochondrial glutathione (GSH). The probe MITO-PQDNs could react rapidly (20 min) with GSH in PBS buffer and exhibited a strong fluorescence signal (586 nm) as well as a significant Stokes shift (200 nm). Moreover, MITO-PQDNs could quantitatively detect GSH with high sensitivity (LOD = 253 nM). Meanwhile, MITO-PQDNs possessed favorable biocompatibility and could detect both endogenous and exogenous GSH in MCF-7 cells. Above all, MITO-PQDNs enabled the detection of fluctuations in mitochondrial GSH concentrations during oxidative stress.